Association between NR3C1 rs41423247 polymorphism and depression: A PRISMA-compliant meta-analysis. Issue 39 (September 2018) - Peng, Qiuju; Yan, Huacheng; Wen, Yuguan; Lai, Chongfa; Shi, Lei
Abstract: Background: A dysfunction of the hypothalamic-pituitary-adrenal (HPA) axis is closely related to the occurrence of depression. The glucocorticoid receptor, also known as the nuclear receptor subfamily 3, group C, member 1 ( NR3C1), provides negative feedback to the HPA axis by binding to glucocorticoids. Some studies have demonstrated an association between the NR3C1 rs41423247 polymorphism and depression, but results from other studies have been controversial. Method: In this study, the association between the NR3C1 rs41423247 polymorphism and depression was evaluated by a meta-analysis using the RevMan 5.3 software, and the Stata 10.0 software was used for sensitivity analysis and publication bias test. According to the inclusion criteria, related studies in databases were retrieved and screened. Results: In total, 9 articles were selected, including 1630 depressed patients and 3362 controls. The meta-analysis showed that homozygous mutation of NR3C1 rs41423247 was associated with depression in the total population (OR = 0.77, 95% CI = 0.64–0.94, P =  .01) and in Caucasians (OR = 0.78, 95% CI = 0.63–0.96, P =  .02). Conclusion: This meta-analysis demonstrates that the NR3C1 rs41423247 homozygous mutation may be a risk factor for depression.